Labeo rohita (Canning of Rohu) in North Indian Style Curry Medium Using polyester-coated Tin Free Steel Cans - A. K. Mallick, T. K. Srinivasa Gopal, C. N. Ravishankar and P. K. Vijayan (Food Science and Technology International 2006; 12; 539, 2006)
Freshwater fish, rohu (Labeo rohita) curry was prepared in a north Indian style, packed in polyestercoated tin free steel (TFS) cans in a 60:40 ratio (fish:curry) and thermal processed in a retort. Physical tests of the can such as double seam efficiency, lacquer integrity, sulphur resistance and food contact application showed that polyester-coated TFS cans can be used for canning fish products. F0 value of the product was 8.79 when the thermal processing was at 121 C for 46.42 min, and cook value to achieve tenderness of the product was 102 min. The processed product was found to be commercially sterile. The product was acceptable even after 6 months of storage at room temperature (282C) and at 37 C withregard to all sensory attributes. Texture attributes such as hardness, chewiness, springiness and cohesiveness did not show marked variation in the samples stored at room temperature and at 37 C. There were no significant changes in chemical parameters during the storage period. The results showed that the polyester-coated TFS cans can be used for processing ready to serve fish products, which can be stored at room temperature for long periods